Drug–herb interactions: a challenge and clinical concern in primary healthcare - M., Sujithra; Puthiyedath, Rammanohar; Pillai, Zeena S. (Frontiers in Medicine, 2025)
Primary healthcare (PHC) is the first level of care that provides basic medical services to people in their own communities. Family doctors, local clinics, and community health centers fall under this category. When it comes to drug–herb interactions, PHC faces unique challenges. Herbal medicine usage is increasing globally, raising the challenge of drug–herb interactions due to simultaneous administration with modern pharmacological agents. Literature on drug–herb interactions is growing but inadequately explored in the context of primary healthcare. This mini review focuses on the concerns and challenges of drug–herb interactions in a primary healthcare setup, taking into consideration patterns, high-risk scenarios, prediction and assessment, and management strategies. It highlights the obstacles faced by primary healthcare practitioners, including time and resource limitations, resource and knowledge gaps, and difficulties in communication. In addition, it emphasizes the need for organized approaches to screen the interactions using risk assessment tools created for primary care and to enhance educational resources to ensure patient safety and medical outcomes in a community-based healthcare setting. A consolidated evidence matrix of drug–herb interactions from published research articles is included, which can serve as a one-stop reference resource at the point of care.